PHASE EQUIVALENT ENERGY-DEPENDENT POTENTIALS-–A SUPERSYMMETRIC APPROACH - Laha, Ujjwal; Behera, Ashwini Kumar; Bhoi, Jhasaketan (Malaysian Journal of Science, 2020)
Phase equivalent potential corresponding to an energy-dependent potential is constructed via the formalism of supersymmetric quantum mechanics and judge the merit of our approach through model calculations.